Beekeeping: Practices, Opportunities and Challenges in Deupur, Parbat, Nepal (ZOO-Journal, 2019)
Beekeeping practice and challenges faced by beekeepers were studied in Deupur, Modi Rural Municipality, Parbat District, Gandaki Province, Nepal. A total of 10 farmers, who had beehives were selected for questionnaire survey during the study period. Of these, five households practiced modern way of beekeeping, two households practiced both modern and traditional way, and three household practiced traditional way of beekeeping. Eighty percent (80%) of respondents supported good forest coverage was the potential opportunities for bee keepers but 20% did not believe; 60% of respondents believed that the existence of a variety of vegetation determined the quality of honey but 40% did not and 20% of respondents were in a reasonable state for availability of resources like hives and storage vessels but 80% did not. The main challenges faced by the beekeepers were expensive modern hives, lack of modern equipments, market instability and pests of bees, such as, ants, moth, mite, wasp, marten and wall lizard. Market stabilization seems to play a provocative role to encourage the people in bee keeping, so, government should pay attention towards it.